Norms in Intercultural Communication between the Javanese and Minang Ethnic in Jorong Timbulun Atas, Regency Solok Selatan - Nofia Ulan Sari; Elida Elida; Yuliarma Yuliarma (Universitas Negeri Yogyakarta, 2025)
Each ethnic group in Indonesia has its own customs and culture that form its identity. The presence of these two ethnic groups in the same geographical area has created interesting social and cultural dynamics to study, particularly in terms of the norms of communication they have established in their daily lives. This study aims to analyze the intercultural communication norms of the Javanese and Minang ethnic groups and identify the strategies used to overcome differences in communication norms. This study uses a descriptive qualitative approach, with data collection conducted through direct observation, in-depth interviews with community leaders from both ethnic groups, and sources from scientific articles. The results of the study found that the Javanese and Minang ethnic communities in Jorong Timbulun Atas use two methods of communication accommodation, namely convergent and divergent adaptation strategies in intercultural communication, with Indonesian as the everyday language because it is a language that can be understood by people of different cultures. It can be concluded that the Javanese ethnic group, with its refined, polite, and gentle characteristics, and the Minang ethnic group, with its assertive nature, can coexist in the same geographical space, creating social dynamics.